THE EFFECTIVENESS OF GUIDED INQUIRY LEARNING ASSISTED BY PhET SIMULATION TO IMPROVE THE CAPABILITY OF REPRESENTATION IMAGE OF SCIENCE STUDENT IN JUNIOR HIGH SCHOOL - Dira Oktaviana; I Ketut Mahardika; Aris Singgih Budiarso (ScienceEdu: Jurnal Pendidikan IPA, 2020)
This study aims to describe the understanding of science concepts of junior high school students in the form of image representation through guided inquiry learning assisted with simulated PhET. This type of research is quantitative descriptive research. The study was conducted at SMP Negeri 2 Genteng. The research subjects were all students of class VIII A and VIII D with a total of 64 student respondents. The collection of data using the test, interview, observation, and documentation techniques. The data analysis technique is to use the Normalized N-Gain test to describe the ability of students' image representation. The results of data analysis showed an increase in understanding of the concept of science in the form of image representation with a value of g = 0.7. In conclusion, that the guided inquiry learning model assisted by the PhET simulation can improve the ability of students' science concepts in the form of Image Representation with high categories, which means that this learning is very effective.